1991
DOI: 10.2307/3869163
|View full text |Cite|
|
Sign up to set email alerts
|

The Tobacco Luminal Binding Protein Is Encoded by a Multigene Family

Abstract: We have cloned cDNAs of the tobacco homolog of the luminal binding protein (BiP) that has been described in other higher eukaryotes. In contrast to the mammalian and yeast protein, tobacco BiP is encoded by a multigene family. The gene products of all the cloned members of this family contain a carboxy-terminal His-Asp-Glu-Leu peptide that may form the signal for retention in the endoplasmic reticulum. Analysis of expression patterns revealed that BiP transcripts are predominantly present in tissues with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
159
1
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(173 citation statements)
references
References 0 publications
11
159
1
2
Order By: Relevance
“…BiP appears to be ubiquitous in all eukaryotic cells and was recently identified within the ER ofwheat endosperm cells (7). Analyses of BiP cloned from several plant species confirmed that the plant proteins also contain the HDEL signal and that this signal functions in the retention ofproteins within the ER (3,4,9,17). Although under normal conditions of BiP expression this protein was shown to retain entirely within the ER, one can still argue that some BiP may escape retention and transport via the Golgi because the HDEL retention signal is known to be saturated (21).…”
Section: Discussionmentioning
confidence: 94%
“…BiP appears to be ubiquitous in all eukaryotic cells and was recently identified within the ER ofwheat endosperm cells (7). Analyses of BiP cloned from several plant species confirmed that the plant proteins also contain the HDEL signal and that this signal functions in the retention ofproteins within the ER (3,4,9,17). Although under normal conditions of BiP expression this protein was shown to retain entirely within the ER, one can still argue that some BiP may escape retention and transport via the Golgi because the HDEL retention signal is known to be saturated (21).…”
Section: Discussionmentioning
confidence: 94%
“…The level of endogenous BiP protein was not elevated more than 20-40% when it was induced by BiP inducer X (BIX) (20). A discrepancy between overexpressed BiP mRNA and BiP protein levels was also reported in Saccaharomyces cerevisiae (30). In this respect, BiP behaves very differently than other ER proteins, such as calreticulin, which can be overexpressed 50-to 100-fold without a divergence between protein and mRNA levels.…”
Section: Discussionmentioning
confidence: 97%
“…As shown in Figure 5, most of the AtELP protein was recovered in the P55 fraction (pellet fractionated at 55,000g), with lesser amounts in both low-speed (P8 and P14) and high-speed (P125) pellet fractions. On the other hand, the marker proteins for ER (BiP, Denecke et al, 1991;AtSEC12, Bar-Peled and Raikhel, 1997), tonoplast (7-TIP, Gomez and Chrispeels, 1993), and PM (RD28, Daniels et al, 1994) were found mostly in the lower-speed pellet fractions (PI, P3, P8, P14). Thus, AtELP had a different fractionation pattern from these endomembrane markers, suggesting that it was not localized in these organelles.…”
Section: Atelp Is An Integral Membrane Protein Found In a Novel Compamentioning
confidence: 99%